Hubungan Karakteristik Ibu Yang Memiliki Bayi Usia 0-24 Bulan Dengan Pengetahuan Tentang Pijat Bayi - Nurseha Nurseha; Dewi Komalasari (Universitas Faletehan, 2020)
Baby massage as a form of touch language has a positive effect on the growth and development of babies. Baby massage can increase levels of the enzyme absorption of gastric and insulin so that food absorption is better, causing babies to starve more quickly, suckle more often and increase milk production. Mothers who have babies need knowledge about baby massage so that mothers can massage with the right techniques. This study aims to determine the correlation between the characteristics of mothers who have babies aged 0-24 months with the mother's knowledge of infant massage at Ciruas Health Center in 2018. This type of research is analytic descriptive with a cross-sectional research design. The population of this research is 152 mothers who have babies aged 24-24 months. A sample of 60 people, the sample was taken by means of Quota sampling from 7 posyandu at the Puskesmas Ciruas. Data collection using questionnaires and direct interviews. The results showed as much as 55% less knowledge. There is a significant relationship between age, parity, education, and occupation of mothers with the mother's knowledge of baby massage. It can be concluded that the mother's characteristics are related to the mother's knowledge about baby massage.